Peningkatan Skala Bisnis dengan Memperluas Cakupan Bisnis, Teknologisasi Pembukuan, dan Optimisasi Operasional - Budiono, Ong William Immatara; Bunawan, Steffi Henny; Tanedi, Seana Tatang; Kenneth, Filbert; Thang, Madeline Vanessa; Amara, Tialini; Tengku, James Arther; Marchalina, Leonis (Journal Pemberdayaan Masyarakat Indonesia, 2025)
KUM042 group was assigned to develop Aulia Cookies, an MSME in Dusun Pajawan, Gandasoli Village, Kramatmulya Subdistrict, Kuningan Regency, West Java, founded by Mrs. Yuyun Sri Wahyuni in 2006. The programs we designed were implemented as a form of community service (PKM). In the initial observation and interview stages, the group identified obstacles in business digitalization, operations, and finance, making it difficult for Aulia Cookies to expand its market. In its development, the group conducted 20 days of on-site assistance at the partner's location and additional follow-up monitoring for 5 months. The activities carried out included: 1) business assistance for MSMEs through product and packaging re-branding; 2) developing promotion and accessing a wider market through social media and marketplaces; 3) implementing more structured business financing. Through these initiatives, it is expected to help Aulia Cookies achieve a significant increase in revenue growth and expand its market reach, supported by broader marketing contributions.